Hydrophobic Drug Release Studies from the Core/Shell Magnetic Mesoporous Silica Nanoparticles and their Anticancer Application: Drug Release Studies from Magnetic Mesoporous Nanoparticles and their Anticancer Application - Hussain, Amina (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Multiple therapeutic hydrophobic drugs can be delivered simultaneously by inorganic, biocompatible iron core mesoporous silica shell nanoparticles. We synthesized superparamagnetic iron oxide nanocrystals encapsulated within mesostructured silica spheres through the sol-gel process. The dose of hydrophobic drugs Paclitaxel (PTX) and Camptothecin (CPT) loading and released on Fe3 O4 @SiO2 core/shell nanoparticle detected by U.V-visible spectrophotometry using a platform of nanoparticles (NPS). After being subjected to external heating, the drug release efficiency of paclitaxel (PTX) and camptothecin (CPT) Fe3 O4 @SiO2 core/shell nanoparticles is increased. Paclitaxel (PTX) and Camptothecin (CPT) Fe3 O4 @SiO2 core/shell nanoparticles did not heat the solution when an alternating magnetic field (AMF) was applied, and there was only mild drug leakage. When compared to Fe3 O4 @MSNs, the nanoparticles (PTX) and (CPT) Fe3 O4 @MSNs function as cancer-targeting mediators, increasing the killing of PANC-1 cancer cells. Human cancer cells were given these therapeutic anticancer water-insoluble drugs with nanoparticles, which is a valuable vehicle for drug delivery, and induced the inhibition of proliferation. Therefore, the goal of this study to emphasize Fe3 O4 @SiO2 core/shell potential as a superior candidate for hydrophobic drug delivery to the PANC-1 cancer cell.